Historiographical Readings on Three Paradigms of the 19th Century: Positivism, Historicism, and Historical Materialism (Interdisciplinary Studies Journal, 2024)
The purpose of this article is to present a comparative overview of schools of thought that contributed to the construction of historical perspectives in the 19th century, attempting to escape, as much as possible, from the historiographical myths surrounding this period in order to analyze the contributions and limitations of three paradigms, namely: Positivism, Historicism, and Historical Materialism. To this end, the contributions of contemporary historians who have aimed to historiographically analyze the production of historical-social knowledge in the 19th century will be of great value.
Keywords: Historiography; 19th Century; Positivism; Historicism; Historical Materialism